Balancing Tradition and Marital Stability: An Interdependence Theory Approach to Jilu Marriage Prohibition - Natasya, Farah Vairuza; Setyobudi, Teguh (Islamic Family Law Study Program, Sharia Faculty, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
Jilu marriage refers to a union between the first and third child in a family. The community of Rejomulyo Village believes that jilu marriage brings misfortune, household instability, and even divorce. Consequently, the prohibition of jilu is preserved as a form of local wisdom aimed at maintaining marital harmony. This study seeks to describe and analyze the concept and implementation of the jilu marriage prohibition in Rejomulyo Village through the lens of interdependence theory. The research employs an empirical legal approach with a sociological juridical perspective, incorporating qualitative data collection methods such as in-depth interviews, field observations, and document analysis. Primary data were obtained from community members using snowball sampling, while secondary data were gathered from literature and legal documents. The findings reveal that jilu in Rejomulyo Village refers to the marriage of the first and third child, which is often accompanied by a ruwatan ritual as a means of warding off misfortune. Analysis through interdependence theory indicates that couples where the first child is male and the third child is female tend to experience greater marital stability compared to those with the reverse composition. This study contributes to a deeper understanding of the interplay between cultural traditions and the psychological dynamics of marriage in traditional communities.